2003
DOI: 10.1002/cncr.11322
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between genetic alteration and long‐term clinical outcome of patients with oligodendroglial tumors, with identification of a consistent region of deletion on chromosome arm 1p

Abstract: BACKGROUND In oligodendroglial tumors, allelic losses on chromosome arms 1p and 19q are not only diagnostic molecular markers but also statistically significant predictors of both chemosensitivity and longer recurrence‐free survival. In the current study, the authors attempted to analyze 21 patients genetically and clinically, with special emphasis on the correlation between genetic alterations and long‐term therapeutic results. METHODS The authors reviewed the clinical cases of 21 patients who had undergone s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
35
0
1

Year Published

2004
2004
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 34 publications
2
35
0
1
Order By: Relevance
“…In this malignant brain tumor, loss of genetic material frequently involves chromosomes 1p and 19q, as likewise documented in the present case [11, 12]. Remarkably, in the family described by Westerhof et al [10], some patients showed mental deficiency or pyramidal tract disease.…”
Section: Discussionmentioning
confidence: 47%
“…In this malignant brain tumor, loss of genetic material frequently involves chromosomes 1p and 19q, as likewise documented in the present case [11, 12]. Remarkably, in the family described by Westerhof et al [10], some patients showed mental deficiency or pyramidal tract disease.…”
Section: Discussionmentioning
confidence: 47%
“…Mapping of occasional tumors with partial LOH have yielded ''regions of minimal deletion'' on 1p36 and 19q13.3, though many of the deletion-defining tumors were not oligodendrogliomas. 54,96,105,106 In line with that hypothesis is the general observation that in contrast to those with whole arm losses, tumors harboring small interstitial deletions tend to have an astrocytic morphology 107 and are often biologically aggressive (unpublished data). Thus, it is unclear that these regions truly harbor oligodendroglioma-specific genes.…”
Section: Oligodendroglial Tumorsmentioning
confidence: 62%
“…3,4 However, despite high specificity, this test has limited sensitivity and is intensive and costly. 5 Furthermore, it requires actual tumor tissue sample from a craniotomy or brain biopsy, making its usefulness in patient surveillance both cumbersome and difficult. A tumor marker from serum or cerebrospinal fluid (CSF) would be easier to collect, quantify, and reproduce and also more practical in clinical practice.…”
Section: Introductionmentioning
confidence: 99%